Pengaruh Pengungkapan Emisi Karbon Terhadap Harga Saham pada Rumah Sakit yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2019-2023 - Fauzi, Alamin; Nusa Bangsa, Ikrar; Ramadhan, Yanuar (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to determine the effect of carbon emissions disclosure on hospital share prices listed on the Indonesia Stock Exchange in 2019-2023. The method used in this research is quantitative descriptive. The sample used in the research was 6 hospitals with a research data period of 5 years, namely 2019-2023. The data analysis techniques used are descriptive analysis, simple linear regression analysis, and hypothesis testing. The research results show that carbon emission disclosure has a positive and insignificant effect on the share prices of hospitals listed on the Indonesia Stock Exchange for 2019-2023.